Effect of manganese and cobalt doping on conductivity of ZnO based varistors: A study by complex plane modulus - Pandey A.; Prasad A.; Singh S.; Parkash O.; Kumar D. (My University, 2025)
Effect of manganese and cobalt doping (0.50 mole%) on electrical properties of ZnO based varistors has been studied using complex plane modulus analysis. It is found that total resistivity of Mn doped sample is more as compared to that of Co doped sample. This has been ascribed to existence of Mn in variable valence states viz. Mn 2+, Mn 3+ and Mn 4+ which promotes hopping conduction leading to increase in the conductivity as compared to Co doped sample, in which Co exists predominantly in +3 state with traces of Co 2+ or Co +4 states. This accounts for its less conductivity. Mechanism of conduction is the same for grains and grainboundaries. © Springer Science+Business Media, LLC 2007.